Characterization and Electron Paramagnetic Resonance Spectra of Two Octahedral Complexes of Copper(II) Vanadate Derived from 1,2-Diaminoethane and 1,2-Diaminopropane - Gopal Narain, (Late); Kumar Jain, Jai (Asian Journal of Chemistry, 2010)
Two complexes of copper(II) vanadate with 1,2-diaminoethane and 1,3-diaminopropane have been prepared. Their analytical and molar conductance data suggest molecular formulae to be [Cu(C2H8N2)3](VO3)2·2H2O and [Cu(C3H10N2)3] (VO3)2·2H2O. The magnetic and spectroscopic data indicate octahedral structure. The EPR data suggest monomeric nature of the complexes.